2022
DOI: 10.5530/pj.2022.14.5
|View full text |Cite
|
Sign up to set email alerts
|

Green and Optimum Extraction of Total Polyphenols Content from Mitragyna speciosa Korth. Havil Leaves using Microwave- Assisted Natural Deep Eutectic Solvent Extraction

Abstract: The current study mainly aims to apply and optimize the microwave-assisted natural deep eutectic solvent extraction (MANDESE) method of total polyphenol content from Mitragyna speciosa (Korth.) Havil leaves using response surface methodology (RSM) and its extraction mechanism using scanning electron microscopy (SEM) imaging. The extraction process was performed using the maceration and MANDESE method. Total polyphenols content was examined using Folin-Ciocalteu reagent and spectrophotometer UV-Vis. The extract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Natural deep eutectic solvents (NaDES) have been increasing in popularity over the last two decades as promising candidates for the green extraction of bioactive compounds from several plant materials since, by varying polarity, viscosity, and extraction temperature, they can be successfully used for the recovery of both polar and non-polar natural products [65][66][67][68][69][70]. They represent a new class of ionic liquid analogs, generally based on mixtures of natural compounds, usually obtained by the complexation of quaternary ammonium salt (working as Hydrogen Bond Acceptor, HBA) with a metal salt or hydrogen bond donor (HBD); this complexation causes the delocalization of the electric charges, resulting in a decrease in the melting point in the mixture relative to the melting points of the individual components [71,72].…”
Section: Nadesmentioning
confidence: 99%
“…Natural deep eutectic solvents (NaDES) have been increasing in popularity over the last two decades as promising candidates for the green extraction of bioactive compounds from several plant materials since, by varying polarity, viscosity, and extraction temperature, they can be successfully used for the recovery of both polar and non-polar natural products [65][66][67][68][69][70]. They represent a new class of ionic liquid analogs, generally based on mixtures of natural compounds, usually obtained by the complexation of quaternary ammonium salt (working as Hydrogen Bond Acceptor, HBA) with a metal salt or hydrogen bond donor (HBD); this complexation causes the delocalization of the electric charges, resulting in a decrease in the melting point in the mixture relative to the melting points of the individual components [71,72].…”
Section: Nadesmentioning
confidence: 99%
“…However, extraction time is an important parameter for the industrial application, and due to prolonged operation, they are difficult to be applied on a large scale and could lead to polyphenols oxidation. Prabowo et al [ 40 ] found that extraction time affected the extraction yield of TPC. Finally, the solvent:solid ratio was slightly low, which can be explained by the mass transfer principles.…”
Section: Resultsmentioning
confidence: 99%